(untitled) (American Journal of Islam and Society, 2005)
Within the context of Islamic thought, suicide has met both tolerance and resistance and has spawned two cultural categories: suicide and martyrdom. Nadia Taysir Dabbagh approaches the issue with a dexterity honed by medical experience, and her insightful analysis of the two concepts reveals that suicide is perceived as a private act condemned by society and religion, while martyrdom is a public act exalted for the greater good. The fusion of theories plucked from psychiatry, anthropology, and psychology and then coupled with compelling case studies conducted in Ramallah and Gaza creates a coverage that treads the line between objective analysis and morbid fascination, as her research contributes a reasoned account of a startling trend largely lost in a region immersed in its tumultuous past and present and uncertain future. This book is the product of an intercalated M.B.–Ph.D. program submitted to the Psychiatry Department at University College London. The introductory chapter incorporates an elucidated methodology that identifies biological, social, and psychological study approaches, with the primary system of analysis resting on the latter. This person-centred technique perceives suicide as an individual phenomenon linked to risk factors (e.g., depression, anxiety, and stressful life events) and associations. Likewise, the social approach favors a broader angle and associates suicide with such social conditions as unemployment, domestic violence, and sociopolitical protest. The biological approach draws a correlation between affective disorders, such as bipolar disorder, and suicide. Eminent suicidologists, such as Michael Kral, Silvia S. Canetto, and David Lester, who assert that suicidal behavior should be placed in its cultural as well as social context, provide the publication’s theoretical foundation ...